Literacy : helping children construc meaning - Cooper, J. David, 1942- (Boston : Houghton Mifflin, 1997)
Understanding literacy: learning and constructing meaning. Developing a balanced literacy program. Activating and developing prior knowledge. The beginning reader and writer...
Keywords: Education; Literacy; Linguistic teaching; Reading comprehension; Reading; Literacy; Reading comprehension